BATAS WAKTU MENSHALATKAN JENAZAH YANG TELAH DIKUBURKAN PERSPEKTIF MAZHAB SYAFI`I DAN HAMBALI - Zul Ikromi; Tasnim Rahman Fitra; Sawil Afli (STIS Darussalam Bermi, 2024)
The scholars of the Madzhab permit funeral prayers to be performed above the grave, but they differ in opinion regarding the time limit of its permissibility. The Shafi'i Madzhab does not specify a time limit for how long after death a funeral prayer can be performed at the grave, unlike the Hambali school, which sets a limit of only one month. This research is qualitative and falls under the category of library research, utilizing a comparative approach. The Shafi'i Madzhab holds the view that there is no time limit for performing the funeral prayer above the grave because the prayer here refers to supplication, which is permissible at any time. This stance is correct as there is no evidence indicating any time restrictions. The Hambali Madzhab contends that the time limit for performing the funeral prayer above the grave is a maximum of one month because many Hadith narrations mention that the Prophet Muhammad (peace be upon him) performed the funeral prayer for Ummu Sa'ad bin Ubadah after she had been buried for a month, and at that time, the body was still considered intact. The most relevant opinion is that of the Shafi'i scholars because there is indeed no evidence restricting the funeral prayer above the grave.